PERFIL SOCIOECONÔMICO, ANTROPOMÉTRICO, DE COMPOSIÇÃO CORPORAL E QUALIDADE DE VIDA DE JOGADORAS UNIVERSITÁRIAS DE FUTSAL EM PERÍODO DE TREINAMENTO E DE COMPETIÇÃO - FREITAS, Nárjara Margarida Teixeira de (2025)
Objective: To evaluate, during the training and competition periods, the socioeconomic, anthropometric, and body composition characteristics and to compare the quality of life of players from two women's futsal teams from São Luis, Maranhão, between the periods. Materials and Methods: This is an analytical, prospective study carried out between April 2023 and September 2024 with the women's futsal team of the Federal University of Maranhão (UFMA) and the women's futsal team of the Jury (OAB) during the training and competition periods. Anthropometric, sociodemographic, economic characteristics, anthropometric and body composition measurements, training frequency, and the Athletes' Quality of Life Questionnaire (QQVA) were collected. The data were analyzed using SPSS (version 26), with the data presented in absolute (n) and relative (%) frequency or mean and standard deviation and median and range (minimum and maximum). Comparisons between training and competition times were performed using the Wilcoxon test and correlations using Spearman's linear correlation, with a significance level of p<0.05. Results: Eighteen female futsal players were evaluated, with a mean age of 30.4±7.6 years, 55.6% with higher education, mainly belonging to social class B (61.1%), 12.2±7.1 years of training time and 10.7±8.1 years of competition. The players had an average weight of 81.3 kg, height of 1.65 m, BMI of 30.0 kg/m2 , 26.0% body fat, 18.5 kg fat mass, and 49.6 kg lean mass. Regarding quality of life, the players presented similar values during training and competition, with results for the training and competition periods, respectively, of 3.1 and 2.4 in the Signs and Symptoms of Overtraining dimension, 3.3 and 3.2 in Basic Conditions for Health, 3.8 and 3.3 in Social Relationships in the Sports Environment, 2.3 and 1.8 in Emotional State of the Athlete, and 2.0 in both moments in the Planning and Periodization of Sports Training dimension. There was no significant correlation between the training frequency and quality of life during training or competition. Conclusion: The findings demonstrated disparate values concerning the sociodemographic and anthropometric profile compared to those observed in other studies conducted in several states. No differences were observed in the dimensions of quality of life between the training and competition periods, nor was there a significant correlation with training frequency.